2019
DOI: 10.3171/2019.4.peds18586
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of open versus endoscope-assisted craniosynostosis surgery

Abstract: OBJECTIVEOpen and endoscope-assisted repair are surgical options for sagittal craniosynostosis, with limited research evaluating each technique’s immediate and long-term costs. This study investigates the cost-effectiveness of open and endoscope-assisted repair for single, sagittal suture craniosynostosis.METHODSThe authors performed a retrospective cohort study of patients undergoing single, sagittal sutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Several studies have established that those undergoing open procedures require longer ICU care. 12,16 This is consistent with findings in this study that ICU length of stay was significantly higher for those undergoing open procedures (P < 0.001) and those with additional risk factors (P < 0.001) (Fig. 1A).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several studies have established that those undergoing open procedures require longer ICU care. 12,16 This is consistent with findings in this study that ICU length of stay was significantly higher for those undergoing open procedures (P < 0.001) and those with additional risk factors (P < 0.001) (Fig. 1A).…”
Section: Discussionsupporting
confidence: 91%
“…12 Socioeconomic determinants such as patient proximity to a helmet orthosis center, access to transportation for these appointments, and time away from work for additional clinic visits may affect the decision to undergo open versus endoscopic surgery. 12 Certain states might have government insurance plans that do not completely cover helmet therapy, which could likewise compound disparities in choosing between surgical modalities. 13 The present study noted that significantly more patients undergoing endoscopic procedures had commercial insurance ( P < 0.001), which is reinforced in single-center studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,16,24,28,32,35,40,42 With an increased focus on cost-effective healthcare delivery, previous studies have shown a significant decrease in financial burden with endoscopic treatment, most often demonstrated in patients with sagittal synostosis. 1,8,19,23,31,39 Fewer data are available on the charges associated with surgical treatment of nonsagittal synostosis (metopic, coronal, and lambdoid), for which traditional open remodeling procedures are distinct from those for sagittal synostosis. Lambdoid synostosis is the least common of these 4 synostosis types, and there is a corresponding paucity of studies including these rare patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever evaluating time-trend sales, inflation could play a confounder role in the relationship between exposure (time) and outcomes (sales) ( Bell, Hadi, Khanal, & Paudyal, 2021 ; Liles et al., 2019 ; Moore et al., 2021 ). The Consumer Price Index (CPI) ( Foster & Ferguson, 2012 ) and Producer Price Index (PPI) ( Livingston, 2011 ) are well-recognized inflation measures, which tends to increase over time ( Liles et al., 2019 ; Moore et al., 2021 ). For instance, during the period of the present study (1992–2019), CPI had positive annual increases in all the years except from 2009.…”
Section: Methodsmentioning
confidence: 99%